Evaluation of 27 different biochars for potential sequestration of antibiotic residues in food animal production environments. Issue 1 (March 2015) - Mitchell, Shannon M.; Subbiah, Murugan; Ullman, Jeffrey L.; Frear, Craig; Call, Douglas R.
Highlights: Biochar prepared at >500 °C sorbed antibiotics better than lower temperature biochar. Ceftiofur sorbed to biochar more than florfenicol. Pinewood biochar prepared at >550 °C sorbed antibiotics in soil–urine–feces slurry. Abstract: The goal of this project was to determine if biochar can be used to sequester antibiotic residues in the environment. Slurries of different biochars ( n  = 27) and water were evaluated for their capacity to adsorb two relatively hydrophilic veterinary antibiotics, florfenicol and ceftiofur. Freely available antibiotic was quantified using HPLC–UV and a bioassay. Biochars prepared at higher pyrolysis temperatures (>500 °C) adsorbed the antibiotics with greater efficiency compared with lower preparation temperatures ( P  < 0.005). Florfenicol was adsorbed (< 99.9%) by six different biochars while ceftiofur was adsorbed by these and nine additional biochars (> 99.98% and > 99.9%, respectively). Florfenicol was sorbed by four biochars (>99.94%) in the presence of soil; however, the sorption performance decreased for two biochars when calf urine and feces were added with the soil. The effect of the biochar proportions on florfenicol sorption in soil–urine–feces slurries were tested with two distinct pinewood biochars, yielding Freundlich sorption coefficients of 2160 and 312 L kg −1 . Pinewood biochar and potentially other types of biochar are excellent candidates for sequestering antibiotic residues in soil–urine–feces environments.